Grandparents Raising Grandchildren: A Crash Course in Child Development - Millie Ferrer-Chancy; Larry F. Forthun; Angela Falcone (EDIS, 2009)
Revised and Expanded! FCS2186-2191, a series of 1-4 page fact sheets by Millie Ferrer-Chancy, Larry Forthun, and Angela Falcone, with contributions by Joe Pergola and Maisie Ross, addresses challenges and issues grandparents may encounter when raising grandchildren. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2009.